RETRACTED: Taguchi-Assisted Optimization Technique and Density Functional Theory for Green Synthesis of a Novel Cu-MOF Derived From Caffeic Acid and Its Anticancerious Activities - Zeraati, Malihe; Mohammadi, Ali; Vafaei, Somayeh; Chauhan, Narendra Pal Singh; Sargazi, Ghasem (Frontiers in Chemistry, 2021)
Taking into account the various applications of the metal organic framework (MOF) in environmental and biological aspects, the preparation of these advanced materials through the use of eco-friendly, fast and low-cost techniques is a hot issue. The organic matter of the aqueous extract of Satureja hortensis was first extracted, which included caffeic acid (CA), gallic acid, quercetin, chlorogenic acid, p-coumaric acid and ferulic acid which are key intermediate in biosynthesis of lignin. As an innovative approach, the Cu-MOF was successfully prepared using a green synthesis technique in which the CA used as a linker to connect the copper and the reaction mechanism is discussed using density functional theory. In order to achieve a discrepancy between the energy levels of the interactive precursor orbitals, the molecules have been optimized using the B3LYP/6-31 G method. Taguchi method was used to optimize the key parameters for the synthesis of Cu-MOF. Cu-MOF has shown anticancer activities against the human breast cancer (MDA-MB-468) cell lines and it could be a potent candidate for clinical applications.